Transformasi Digital Industri Perbankan Syariah Indonesia - Husni Shabri (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2022)
Digital banking transformation is an important issue in the banking industry today. Digital disruption has changed the way people do business and transact. However, there are still many problems faced in carrying out digital transformation. The purpose of this study is to analyze the digital transformation process in the Islamic banking industry in Indonesia and its impact on the development and growth of Islamic banks. The research method uses descriptive qualitative approach with Systematic Literature Review. Data were collected from scientific literature references, books and reports from official institutions. The results of the study indicate that the process of accelerating digital transformation in Islamic banking is accelerated by the COVID-19 pandemic. This condition requires Islamic banking to make digital transformation a priority and strategy in an effort to increase bank competitiveness. Digital transformation has an impact on the development of Islamic banks with the increasing number of customers and total assets, many Islamic commercial banks providing digital services and the existence of Islamic banks that operate purely digitally.